Natural Fungal Endophytes From Noccaea caerulescens Mediate Neutral to Positive Effects on Plant Biomass, Mineral Nutrition and Zn Phytoextraction - Yung, Loïc; Sirguey, Catherine; Azou-Barré, Antonin; Blaudez, Damien (Frontiers in Microbiology, 2021)
Phytoextraction using hyperaccumulating plants is a method for the remediation of soils contaminated with trace elements. As a strategy for improvement, the concept of fungal-assisted phytoextraction has emerged in the last decade. However, the role played by fungal endophytes of hyperaccumulating plants in phytoextraction is poorly studied. Here, fungal endophytes isolated from calamine or nonmetalliferous populations of the Cd/Zn hyperaccumulator Noccaea caerulescens were tested for their growth promotion abilities affecting the host plant. Plants were inoculated with seven different isolates and grown for two months in trace metal-contaminated soil. The outcomes of the interactions between N. caerulescens and its native strains ranged from neutral to beneficial. Among the strains, Alternaria thlaspis and Metapochonia rubescens, respectively isolated from the roots of a non-metallicolous and a calamine population of N. caerulescens, respectively, exhibited the most promising abilities to enhance the Zn phytoextraction potential of N. caerulescens related to a significant increase of the plant biomass. These strains significantly increased the root elemental composition, particularly in the case of K, P and S, suggesting an improvement of the plant nutrition. Results obtained in this study provide new insights into the relevance of microbial-assisted phytoextraction approaches in the case of hyperaccumulating plants.